2021
DOI: 10.3390/plants10050923
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Strain Bacillus subtilis 26D Increases Levels of Phytohormones and Repairs Growth of Potato Plants after Colorado Potato Beetle Damage

Abstract: Plant damage caused by defoliating insects has a long-term negative effect on plant growth and productivity. Consequently, the restoration of plant growth after exposure to pathogens or pests is the main indicator of the effectiveness of the implemented defense reactions. A short-term Leptinotarsa decemlineata Say attack on potato tube-grown plantlets (Solanum tuberosum L.) led to a reduction of both the length and mass of the shoots in 9 days. The decrease of the content of phytohormones—indole-3-acetic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…Microbial inoculants particularly plant growth promoting microorganism (PGPM) is one of the most efficient soil bacteria for promoting plant growth and development [215,263]. PGPM can benefits plants in three mechanisms: (i) Biofertilizer (i.e., N 2 -fixing bacteria and phosphate-solubilizing bacteria) to aid in plant nutrient absorption by delivering fixed nitrogen or other nutrients [264]; (ii) Phytostimulators that can stimulate plant growth by creating plant hormones [264][265][266]; and (iii) Biological control agents to protect from phythopathogenic organisms and abiotic stress [264]. However, positive microbial inoculants may transiently affect microbial biomass [267], and the rise in activity or biomass may be triggered by native inhabitants preying on the freshly introduced microbes [268].…”
Section: Fertilizermentioning
confidence: 99%
“…Microbial inoculants particularly plant growth promoting microorganism (PGPM) is one of the most efficient soil bacteria for promoting plant growth and development [215,263]. PGPM can benefits plants in three mechanisms: (i) Biofertilizer (i.e., N 2 -fixing bacteria and phosphate-solubilizing bacteria) to aid in plant nutrient absorption by delivering fixed nitrogen or other nutrients [264]; (ii) Phytostimulators that can stimulate plant growth by creating plant hormones [264][265][266]; and (iii) Biological control agents to protect from phythopathogenic organisms and abiotic stress [264]. However, positive microbial inoculants may transiently affect microbial biomass [267], and the rise in activity or biomass may be triggered by native inhabitants preying on the freshly introduced microbes [268].…”
Section: Fertilizermentioning
confidence: 99%
“…Bacillus aryabhattai, Achromobacter denitrificans, and Ochrobactrum intermedium were isolated, which grew at 2.60 mol/L salt concentration and showed higher nitrogen fixation potential, phosphate solubilization, and IAA production at 200 mM salt stress (Sultana et al, 2021). Similarly, Bacillus amyloliquefaciens and B. subtilis were found to produce phytohormones such as gibberellins and indole acetic acid (Shao et al, 2015;Sorokan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokinins such as zeatin produced by Bacillus play a pivotal role in maintaining cellular proliferation and differentiation [ 83 ]. A study by Hussain and Hasnain [ 84 ] showed that the extracts obtained from cell cultures of B. licheniformis and B. subtilis are capable of increasing the weight and size of cucumber cotyledons separated from the seedlings, by inducing plant cell division due to the presence of cytokinins zeatin and zeatin ribose thus enhancing tolerance to salt stress.…”
Section: Bacillus Spp Confers Protection To the Plant From E...mentioning
confidence: 99%